HE ASSESSMENT OF SUSTAINABLE DEVELOPMENT FACTORS IN THE RURAL AREAS - A CASE STUDY FROM AZERBAIJAN - Fariz ALAKBAROV; Sait ENGINDENIZ; Ramina MUSTAFAYEVA; Muhammad ALAKBAROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural development is the effort to ensure the economic, social, and cultural development of these communities in a democratic way, by first creating a sense of need for individuals and communities living in rural areas and making their living from the agricultural sector or similar rural occupations. For improving and optimizing Sustainable Development Goals (SDGs) approaches for rural livelihoods, it is essential firstly to monitor and evaluate the current situation on SDGs in target villages and its achievements, also to identify the challenges and opportunities in this area. The purpose of study is to conduct surveys for assessment of current situation on SDGs and identifying opinions and understandings of farmers/producers and extension providers/input suppliers on this issue in farms located in Tovuz, Agstafa, Gadabay and Tartar districts in Azerbaijan. In the study, primary clients were farmers and secondary clients were extension providers/input suppliers including different representatives from the public and private sectors. During study, we identified the main pre-conditions, such as the technical, finance and economic problems, natural resources and hazards that farmers face in agriculture, as well as main difficulties faced by farmers in accessing agricultural extension services/trainings, also annual production volume and income on the farm and other difficulties faced by farmers for achievement of SDGs in farms. In the study, data were collected by face-to-face survey method from 47 farmers and 5 extension providers selected by random sampling from Tovuz, Agstafa, Gadabay and Tartar districts. Simple statistical methods were applied in the evaluation of the data obtained, and average and percentage calculations were performed. According to the results, farmers are facing some challenges preventing the achievement of SDGs such as finance and economic problems, natural resources and hazards, and technical issues in agriculture. To eliminate the negative effects of urbanization in target villages, there is a great need to improve rural income sources and promote employment for people in rural areas.